The Role of Working Memory, Short-Term Memory, Speed of Processing, Education, and Locality in Verb-Related Morphosyntactic Production: Evidence From Greek - Fyndanis, Valantis; Masoura, Elvira; Malefaki, Sonia; Chatziadamou, Efpraxia; Dosi, Ifigeneia; Caplan, David (Frontiers in Psychology, 2022)
This study investigates the relationship between verb-related morphosyntactic production (VRMP) and verbal Working Memory (WM), nonverbal/visuospatial WM, verbal short-term memory (STM), nonverbal/visuospatial STM, speed of processing, and education. Eighty healthy middle-aged and older Greek-speaking participants were administered a sentence completion task tapping into production of subject-verb agreement, time reference and grammatical aspect, and cognitive tasks tapping into verbal STM, nonverbal/visuospatial STM, verbal WM, nonverbal/visuospatial WM, and speed of processing. Aspect elicited significantly worse performance than time reference and agreement, and time reference elicited significantly worse performance than agreement. There were significant main effects of verbal STM/WM and education: the greater the participants’ verbal STM/WM capacity, and the higher their educational level, the better their performance on VRMP. Moreover, verbal WM affected aspect and time reference significantly more than agreement. These results corroborate earlier findings that verbal WM is involved in VRMP, and interacts with it. That verbal WM/STM (but not nonverbal STM/WM) were found to subserve VRMP suggests that VRMP is predominantly supported by domain-specific, not domain-general, memory resources. The significant main effects of verbal WM and verbal STM suggest that both the processing and storage components of WM are relevant to VRMP. That verbal WM (but not verbal STM) interacts with the production of aspect, time reference and agreement suggests that aspect and time reference are computationally more demanding than agreement. These findings are consistent with earlier findings that, in persons with aphasia, verbal WM interacts with the production of grammatical aspect, time reference and subject-verb agreement.